Role of Adiponectin Hormone Concentrations and Some Immunological and Biochemical Parameters inAlloxan Induced Diabetic Male Rabbits and Diabetic Treated with Alpha Lipoic Acid and L-Carnitine - Mohanad Hasan Mahmood Humadi Al-Izzi; Zaid Mohamad Mubarak; Ismat Jamal Jamil (Tikrit Journal of Pure Science, 2023)
This study was designed in order to estimate the effect of alloxan induced diabetes mellitus on adiponectin hormone concentration and some immunological and biochemical parameters of male domestic rabbits. The study involved  (20) blood samples were divided into 4 groups : group one: adult normal healthy male rabbits as control group, group two: adult male rabbits with alloxan induced diabetes mellitus, group three: adult male rabbits with alloxan induced diabetes mellitus treated with alpha lipoic acid (100 mg/kg), group four: adult male rabbits with alloxan induced diabetes mellitus treated with L-carnitine (100 mg/kg). The results of this study found significant decrease in adiponectin hormone concentrations at levels (P≤ 0.05) in second group as compared with control group; while significant increase in adiponectin hormone concentrations at levels (P≤0.05) in third and fourth groups in comparison with diabetic group, and there is significant increase in proinflammatory cytokine Interleukin 1 β (IL-1β) concentrations at levels (P≤ 0.05) of second group in comparison with control group, while significant decrease in IL-1 β concentrations at levels (P≤ 0.05) of third and fourth groups in comparison with diabetic group; and there are significant increases in the activity of enzymes: Alanine amino transferase (ALT), and Aspartate amino transferase (AST) at levels (P≤ 0.05) of second group in comparison with control group, while significant decrease in the activity of enzymes: Alanine amino transferase (ALT), and Aspartate amino transferase (AST) at levels (P≤ 0.05) of third and fourth groups in comparison with diabetic group.